2014
DOI: 10.7314/apjcp.2014.15.16.6665
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Features and Molecular Subtypes of Breast Cancer in Young Women (Age ≤35)

Abstract: Asian Pac J Cancer Prev, 15 (16), 6665-6668 IntroductionBreast cancer is the most frequent cancer among women and it is the second leading cause of cancer death around the world (Ferlay et al., 2010;DeSantis et al., 2011). Breast cancer in women under 40 years is not a common condition. However, prevalence of breast cancer in pre-menopausal women has been increasing in several countries over the last years (Cardoso et al., 2012;Keramatinia et al., 2014). Around 6.6% of all breast cancer cases are diagnosed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 30 publications
4
16
1
3
Order By: Relevance
“…BCS has been shown to provide local control similar to mastectomy in young patients (18). Nevertheless, it has been published that the most frequently performed surgical procedure for breast cancer in patients under 35 years of age was mastectomy (19). The mastectomy rate in our study was found to be higher in young patients as compared to the postmenopausal group.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…BCS has been shown to provide local control similar to mastectomy in young patients (18). Nevertheless, it has been published that the most frequently performed surgical procedure for breast cancer in patients under 35 years of age was mastectomy (19). The mastectomy rate in our study was found to be higher in young patients as compared to the postmenopausal group.…”
Section: Discussionmentioning
confidence: 40%
“…In our study, significantly higher rates of grade 3 tumors and Ki-67 rates were identified in the younger patients. Göksu et al (19) reported that luminal B was the most common molecular subtype in breast cancer patients 35 years of age and younger. In addition,triple negative breast cancer rates have been reported to be high in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(16) ise genç yaş grubunda yapılan cerrahi tipinin prognozda etkili olmadığını vurgulamış-lardır. Meme kanserinin tedavisinde yaş MKC için bir kontraendikasyon değildir (17) . Genç hasta grubunda MKC'nin mastektomi kadar yerel kontrol sağladı-ğı gösterilmiştir (18) .…”
Section: Discussionunclassified
“…Göksu ve ark. 'nın (17) yaptığı çalışmalarda, 35 yaş ve altı meme kanserli hastalarda Luminal B'nin en sık görülen moleküler alt tip olduğu yayınlandı. Benzer şekilde Collins ve ark.…”
Section: Discussionunclassified